Description of Nate Macauley’s Character in One of Us Is Lying Novel by Karen M. Mcmanus - Anjani, Neneng Sri (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
This research discusses about description of Nate Macauley’s character in One of Us Is Lying novel by Karen M, McManus. The focus of study is how the description of Nate Macauley’s character in One of Us Is Lying novel by Karen M, McManus. The research method used in this study is a descriptive qualitative method with an objective approach. The results of this study found that Nate Macauley was described analytically, as a figure who has dark hair, tall thin body, sharp cheekbones and eyes far apart with dark eyelashes. The character of Nate Macauley who is portrayed directly is sensitive, ignorant, easygoing, mischievous, outspoken and also useful in emergency situations and reliable. While in a dramatic way Nate Macauley is portrayed by the author through actions and dialogue which explains that he has a mischievous character but relaxed, stubborn, playboy, and also described as a figure who is always alert, clever, caring and a bit humorous. Keywords: Nate Macauley, One of Us is Lying Novel, Character Depiction